Effect of A-site cation on crystal structure and microwave dielectric properties of AGe4O9 (A = Ba, Sr) ceramics. Issue 7 (July 2021) - Li, Feihu; Tang, Ying; Li, Jie; Fang, Weishuang; Ao, Laiyuan; Wang, Yu; Zhao, Xiangguang; Fang, Liang
Abstract: AGe4 O9 (A = Ba, Sr) ceramics with hexagonal structure were fabricated by solid-phase reaction. BaGe4 O9 sintered at 1060 °C had low εr ∼9.8, high Q × f ∼78, 400 GHz and τf ∼ -44.2 ppm/°C, whilst SrGe4 O9 sintered at 1100 °C exhibited relatively high εr ∼11.2, low Q × f ∼62, 500 GHz and near-zero τf ∼ -11.7 ppm/°C. The τf of SrGe4 O9 was nearer to zero than that of BaGe4 O9 due to the smaller τε value and the smaller distortion of the [GeO6 ] octahedrons. The 'rattling' cations at A-site contribute to comparatively high εr, low Q × f and near-zero τf values in Sr1- x Ba x Ge4 O9 ceramics. This work presents a new idea of adjusting the microwave dielectric performance (MDP) of ceramics by changing the strength of the rattling effect at A-site.